Partnerstwo lokalne w ekonomii społecznej jako nowy paradygmat budowania spójności społecznej ​ - Łojko, Majka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The social economy has been trying to recognize its partnering role by the public and business sectors over recent years. The results are visible in the increasing use of its instruments in policy implemented by both the government and the regional authorities. The essence of local partnership is one of the key issues inherent in the new paradigm of building social cohesion and is a tool for a new economic and social order. The task of local partnership, understood as a kind of relationship between public entities, business and non-governmental organizations based on the principles of dialogue, reciprocity and equivalence, is to combine knowledge, experience and initiatives of various people and institutions in solving social problems.